(untitled) (Research, Society and Development, 2024)
The human papillomavirus (HPV) belongs to the Papillomaviridae family, and its life cycle is directly linked to the differentiation of the host’s epithelial cells. More than 200 types of the virus have been detected and can lead to the development of different types of benign and malignant epithelial tumors. This virus has tropism for skin tissue and mucous membranes. HPV types are classified as low-risk and high-risk; HPV is currently predicted to be the main risk factor for carcinomas and lesions of the oral cavity and oropharynx. The discovery of the association between HPV and oropharyngeal carcinoma is relatively recent and it is known that the profile of affected patients is different from the profile of patients typically affected by other tumors of the head and neck region. This work aimed to evaluate the association of high-risk HPV in the etiology of head and neck carcinomas. This was a systematic review study. Data collection was carried out through published scientific articles, using the following descriptors: Human Papilloma Virus (HPV), Oral Cavity and Oropharyngeal Cancer, through searches in the SciELO, PUBMED and GOOGLE ACADEMICO databases. Articles from 2010 to 2023. Patients affected by oropharyngeal tumors in relation to HPV are younger patients and the prevalence was higher in age groups of 41-50 years. The most frequent genotype found was HPV16, considered the high-risk type.